Silica Bonded S-Sulfonic Acid: A Recyclable Catalyst for the Synthesis of Quinoxalines at Room Temperature - Khodabakhsh Niknam; Maleki Mohagheghnejad; Dariush Saberi (Molecules, 2009)
The reaction of 3-mercaptopropylsilica (MPS) and chlorosulfonic acid in chloroform afforded silica bonded S-sulfonic acid (SBSSA), which was used as a catalyst for the room temperature synthesis of quinoxaline derivatives from 1,2-diamino compounds and 1,2-dicarbonyl compounds. The catalyst could be recycled and reused several times without any loss of efficiency.